Chronic Insomnia Is Associated with Higher Circulating Interleukin-8 in Patients with Atherosclerotic Cerebral Small Vessel Disease - Wang J (Dove Medical Press, 2020)
Jihui Wang,1 Xiaodong Chen,2 Xuejiao Men,2 Minhua Chen,1 Jiong Tao,1 Zhengqi Lu2 1Department of Psychiatry, the Third Affiliated Hospital, Sun Yat-Sen University, Guangzhou 510630, People’s Republic of China; 2Department of Neurology, the Third Affiliated Hospital, Sun Yat-Sen University, Guangzhou 510630, People’s Republic of ChinaCorrespondence: Jiong TaoDepartment of Psychiatry, The Third Affiliated Hospital, Sun Yat-sen University, No.600 Tianhe Road, Tianhe District, Guangzhou, Guangdong 510630, People’s Republic of ChinaTel +8613600071635Email tj2023@163.comZhengqi LuDepartment of Neurology, The Third Affiliated Hospital, Sun Yat-sen University, No.600 Tianhe Road, Tianhe District, Guangzhou, Guangdong 510630, People’s Republic of ChinaTel +8618922102767Email lzq1828@outlook.comObjective: Chronic inflammatory responses and leukocyte infiltration are classical pathological features of cerebral small vessel disease (CSVD). To date, limited evidence of a relationship between chronic insomnia and inflammatory responses in patients with CSVD has been uncovered. The purpose of the present study was to investigate the potential relationship between chronic insomnia and pro-inflammatory cytokine levels in patients with atherosclerotic CSVD (A-CSVD).Methods: In total, 76 A-CSVD patients with or without chronic insomnia (CI) confirmed using magnetic resonance (MR) were prospectively recruited. Overnight polysomnography (PSG) was performed and serum levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, IL-17A, IL-8, and IL-12 assessed. Cytokine levels were compared between CSVD+CI (study group) and CSVD without CI (control group) patients, and the correlations between PSG parameters and cytokine levels were explored in all patients via multiple linear regression analyses.Results: The serum IL-8 level of the study group (12.3± 4.4 pg/mL) was significantly higher than that of the control group (7.5± 2.2 pg/mL; P< 0.05). PSG measurements showed that patients in the study group had significantly higher sleep onset latency (SOL), arousal index (ArI) and wake after sleep onset (WASO) as well as lower total sleep time (TST), sleep efficiency (SE) and stage 3 NREM sleep (N-3) ratio, compared with the control group (P< 0.05). Multiple linear regression analyses led to the identification of ArI (β=0.026, P< 0.05) and TST (β=− 0.054, P< 0.05) as significant positive and negative predictors of the IL-8 level, respectively.Conclusion: Chronic insomnia, in particular, sleep fragmentation and short sleep duration, may be involved in promotion of serum IL-8 expression in patients with atherosclerotic CSVD.Keywords: cerebral vascular disease, sleep, polysomnography, fragmentation, markers